ASSESSMENT OF KNOWLEDGE AMONG NURSES REGARDING CENTRAL LINE ASSOCIATION BLOOD STREAM INFECTION - FAROOQ , R; BATOOL , S; TASNEEM , SS; JABEEN , R (Biological and Clinical Sciences Research Journal, 2024)
Central line-associated bloodstream infections (CLABSIs) pose a serious health risk in hospital settings, leading to increased morbidity, mortality, and healthcare costs. Nurses play a crucial role in CLABSI prevention; however, knowledge gaps can hinder their ability to adhere to best practices, especially in resource-limited settings like Pakistan. Objective: This study aims to assess the knowledge and confidence of nurses at Jinnah Hospital, Lahore, regarding CLABSI prevention, identifying key areas that require targeted educational interventions. Methods: A cross-sectional descriptive design was used to capture knowledge levels among 300 nurses at Jinnah Hospital, Lahore. The participants, aged 25-50 years and with at least one year of ward experience, completed a structured, self-administered questionnaire focusing on core CLABSI prevention practices. Purposive sampling was employed, and data were analyzed using SPSS to generate descriptive and inferential statistics. Ethical approval and informed consent were obtained prior to data collection. Results: The findings revealed significant variability in nurses’ knowledge and confidence regarding CLABSI prevention practices. While the majority demonstrated understanding in some areas, key gaps persisted, particularly in the use of aseptic techniques, proper catheter maintenance, hand hygiene adherence, and awareness of advanced preventive measures like antibiotic-coated catheters. Approximately 20% of respondents expressed low confidence in critical aspects of CLABSI prevention, aligning with previous literature on knowledge gaps in similar resource-constrained environments. Conclusion: This study highlights the need for targeted educational interventions focused on CLABSI prevention among nursing staff in Pakistan. Enhanced training on aseptic practices, regular refresher courses, and practical workshops are recommended to standardize infection control measures and bolster nurse confidence, ultimately aiming to reduce CLABSI incidence and improve patient outcomes.